Adoption of improved chickpea technologies in North Gondar zone of Ethiopia: The case of Gondar Zuria District - Fenta, M. (University of Gondar, 2017)
Adoption of improved technologies is seen as a key driver to increase agricultural production and productivity in Ethiopia. Considerable efforts have been made by government and NGOs to disseminate improved technologies in order to boost production and productivity chickpea though the outcome is not impressive. The purpose of this study was to analyze drivers of chickpea technologies adoption and farmers’ preference to adopt chickpea in Gondar Zuria district. This study used cross-sectional data in 2015/16 production season from the sample of 224 household heads selected through multi-stage sampling technique. Descriptive and econometrics models were employed to analyze the data. Tobit model was used to identify factors affecting adoption decision. FTC distance, farm income, livestock owned, agricultural training and credit access have significantly affected the adoption of improved chickpea varieties. Age, experience, livestock holding, number of people rely on, field days, trainings, market and road distances have significantly influenced the adoption of bio-inoculant fertilizer. Age, family size, asset holding, land size, number of people rely on, sex, education status, radio ownership, agricultural training and perception have significantly influenced the adoption of chemical fertilizer. An Ordered Probit model was also used to identify levels of adoption of improved chickpea technologies. These are non-adopters (36.6%), low adopters (31.3%), medium adopters (24.1%) and high adopters (8.0%) of improved chickpea technologies. The result indicates that farm income, livestock size, agricultural training, credit access and FTC distance have significantly influenced levels of adoption of improved chickpea technologies. Conjoint analysis was used to know farmers’ preference on the improved chickpea technologies. The result indicates that variety, payment option, chemical fertilizer and bio-inoculant have 45%, 28%, 14% and 13% share of relative importance, respectively. Shasho variety, DAP fertilizer, bio-inoculant and 50% pre-payment as a package has the highest preference value and ranked the first from different packages. Based on the findings, government and NGOs should give emphasis on strengthen field days and trainings, the provision education, encouraging livestock rearing, strengthening credit access, encouraging farmers’ cooperative, strengthening rural infrastructure, promoting resource endowment, and arranging experience sharing. Lastly, Shasho, DAP fertilizer and bioinoculant with credit access are preferred and should be promoted more in the study area.